Conversion and contagion in entrepreneurship: A cross-country analysis - Marco Bade (Strategic Entrepreneurship Journal, 2021)
Consistent with the theories of planned behavior and social contagion, this study is based on the notion that entrepreneurial intentions affect entrepreneurial behavior ("conversion channel"), which in turn affects others' intentions ("contagion channel"). GMM estimation results of a simultaneous equation model suggest that entrepreneurial intentions and new business ownership are reciprocally related. The conversion channel appears to be the stronger force in the relationship. Additional moderator analyses suggest that environmental munificence, as expressed by regulatory quality, advanced stage of the economy, and economic growth strengthen, whereas the GDP level weakens the relationship. Furthermore, entrepreneurial perceptions, exits, and knowing other entrepreneurs promote the conversion channel but mitigate the contagion channel. These findings yield implications relevant for research and policy makers. Managerial Summary A positive feedback loop in the economy is a situation where two events reinforce each other. In such situation, small and random changes in the economy, such as policy changes or economic shocks, are magnified. This study shows that there is a positive feedback loop in entrepreneurship between entrepreneurial intentions and behavior: individuals' entrepreneurial intention determines actual entrepreneurial behavior, which in turn encourages others to develop entrepreneurial intentions. The positive feedback loop is strengthened by environmental munificence, weakened by living standards, and ambiguously affected by entrepreneurial perceptions, experience, and networks. These findings deepen our understanding of how startup hotspots emerge, emphasize the importance of accounting for structural influences, and contribute to the discussion on cross-country variation in entrepreneurial activity.
Keywords: 650; conversion; entrepreneurial intentions; new business ownership; social contagion; theory of planned behavior